Sentinel Lymph Node Biopsy and Nodal Ultrastaging in Colorectal Cancer. Issue 1 (January 2015) - Huynh, Kelly T.; Bilchik, Anton J.
<x xml:space="preserve">Abstract</x> Abstract The tumor status of the regional lymph nodes is the most important prognostic indicator in colorectal cancer (CRC), as it is in other solid tumors. Sentinel lymph node biopsy (SLNB), which has profoundly impacted the treatment of melanoma and breast cancer, has been applied in CRC in an attempt to improve nodal staging accuracy. The challenge lies in identifying patients who have tumor-negative nodes but are at high risk of regional or distant failure and therefore may benefit from adjuvant chemotherapy. Because standard pathological analysis of lymph nodes may incorrectly stage colon cancer, multiple studies have investigated nodal ultrastaging based on identification and immunohistochemical and/or molecular assessment of the sentinel node. This review focuses on the technique of SNLB, its feasibility and validity, and the controversies that remain regarding the clinical significance of nodal ultrastaging in CRC.